Below‐bandgap absorption in InAs/GaAs self‐assembled quantum dot solar cells. (29th May 2014) - Li, Tian; Dagenais, Mario
Abstract A new approach to derive the below‐bandgap absorption in InAs/GaAs self‐assembled quantum dot (QD) devices using room temperature external quantum efficiency measurement results is presented. The significance of incorporating an extended Urbach tail absorption in analyzing QD devices is demonstrated. This tail is used to evaluate the improvement in the photo‐generated current. The wetting layer and QD absorption contributions are separated from the tail absorption. Several absorption peaks due to QD excited states and potentially different size QDs are observed. An inhomogeneous broadening of 25 meV arising from the variance in the size of QDs is derived. Copyright © 2014 John Wiley & Sons, Ltd.